Tax Administration and Revenue Generation: A Perspective of Osun Internal Revenue Service - Adebayo, Aderemi Olalere; Adeyemi, Adewumi Zaid; Osunwole, Olatunji Oludayo (EuroEconomica, 2022)
Objectives: The main aim of this study is to examine the influence of tax administration on government revenue generation of Osun State, Nigeria. The specific objectives are to evaluate the shortage of staff and inadequate training of available tax collectors on revenue generation and investigate how the improper records and account keeping of revenue officers affect the revenue generation. The study gives an insight for revenue agencies to recruit professionals to manage the tax administration. Prior work: This study relates to outcome shows the tax administration in Lagos state is not efficient due to inadequate training of tax officers. Approaches: Descriptive survey design and purposive sampling technique were employed. A total of 187 respondents participated in the study. Questionnaires were used to gather the data while descriptive and inferential statistics were used to analysed data. Results: The result shows that shortage and inadequate training of staff and improper records and accounting keeping had a negative and significant influence on revenue generation. Implication: These can pose challenges on government not to fulfill its obligation thereby leading to a source of external financing. Value: Effective tax administration system enhances revenue generation by getting the right personnel, practice and laws to guide tax administration.